Age Limit for Regional Head Candidates and Legal Considerations from the Supreme Court Decision No. 23 P/HUM/2024 and Constitutional Court Decision No. 70/PUU-XXII/2024 - Sarjiyati Sarjiyati; Taufiq Yuli Purnama; Anik Tri Haryani; Endang Murti; Izyan Farhana Zulkarnain; Vivi Frita Trisnani (Universitas Muhammadiyah Surakarta, 2025)
ABSTRACT Purpose of the Study: This research aims to analyze the legal consideration that influence differences in a Supreme Court Decision and a Constitutional Court Decision in the Regional Head Election process in 2024, and these decisions’ implications on the age limit for regional head candidates in the 2024 regional general election in creating checks and balances in the government. Methodology: This research utilizes the normative legal research method with the jurisprudential approach, statute approach, conceptual approach, and analytical approach. The data were descriptively analyzed to obtain the research results on the interpretation of age limits for regional head candidates in the 2024 regional general election in the two decisions, namely the Decision of the Supreme Court No. 23P/HUM/2024 and the Decision of the Constitutional Court No. 70/PUU-XXII/2024. These differences led to a lack of legal certainty and a misalignment with the general principle of good governance that is in line with the checks and balances principle in the government. Results: The Decision of the Supreme Court No. 23P/HUM/2024 determines that the age limit for regional head candidates is calculated since the inauguration, while the Decision of the Constitutional Court No. 70/PUU-XXII/2024 regulates that it is calculated since the determination of candidate pairs. Such differences led to a lack of legal certainty, which impacts the implementation of the 2024 Regional Head Election. The legal implications are that these differences may potentially disturb the democratic and political participation processes, especially for the younger generation. The 2024 Regional Head Election applied the Decision of the Constitutional Court No. 70/PUU-XXII/2024, which regulates that the minimum age of regional head candidates is 30 years old for candidate governors and candidate vice governors, and a minimum of 25 years old for candidate regents, candidate vice regents, candidate mayors, and candidate vice mayors. This is calculated since the determination of candidate pairs, as they have passed the stages of the 2024 Regional Head Election. Applications of this Study: The state institution and the government are expected to be more careful when issuing interpretations through decisions that equally have final, binding, and erga ormes characteristics to prevent the occurrence of a lack of legal certainty. There should be efforts to align regulations to prevent legal dualism, which may lead to conflicts and issues in society. Novelty/Originality of this Study: It provides an analysis of the Decision of the Supreme Court No. 23P/HUM/2024 and the Decision of the Constitutional Court No. 70/PUU-XXII/2024 on the age limit for regional head candidates and the implications of these decisions in creating governmental checks and balances. Keywords: Decision, age limit, regional head election, checks and balances. ABSTRAK Tujuan Penelitian: Penelitian ini bertujuan untuk mengetahui perbandingan pertimbangan hukum yang mempengaruhi perbedaan dalam putusan Mahkamah Agung dan Mahkamah Konstitusi dalam proses Pemilihan Kepala Daerah tahun 2024 dan implikasi putusan Mahkamah Agung dan Mahkamah Konstitusi dalam ambang batas usia calon kepala daerah pada Pemilihan Kepala Daerah tahun 2024 dalam menciptakan checks and balances di pemerintahan. Metode: Penelitian ini menggunakan metode penelitian hukum normatif dengan menggunakan pendekatan yurisprudensi, pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan analisis. Data dianalisis secara deskriptif hingga diperoleh hasil penelitian bahwa perbedaan pada kedua putusan, baik Putusan Mahkamah Agung Nomor 23P/HUM/2024 dan Putusan Mahkamah Konstitusi Nomor 70/PUU-XXII/2024, dalam penafsiran ambang batas usia calon kepala daerah tahun 2024 berakibat pada ketidakpastian hukum dan ketidaksesuaian dengan asas umum pemerintahan yang baik yang sejalan dengan prinsip checks and balances pemerintahan. Hasil penelitian: Putusan Mahkamah Agung Nomor 23 P/HUM/2024 menetapkan bahwa usia calon kepala daerah dihitung sejak pelantikan, sedangkan Putusan Mahkamah Konstitusi Nomor 70/PUU-XXII/2024 menyatakan bahwa usia dihitung sejak penetapan pasangan calon. Perbedaan ini menciptakan ketidakpastian hukum yang berdampak pada pelaksanaan Pilkada 2024. Kedua lembaga memiliki argumen hukum dan ada implikasi dari putusan tersebut terhadap sistem checks and balances dalam pemerintahan. Perbedaan pandangan antara Mahkamah Agung dan Mahkamah Kosntitusi tidak hanya mencerminkan ketidakpastian hukum, tetapi juga berpotensi mengganggu proses demokrasi dan partisipasi politik, terutama bagi generasi muda. Pelaksanaan Pilkada tahun 2024 menggunakan Putusan Mahkamah Konstitusi Nomor 70/PUU-XXII/2024, yang mengatur bahwa usia calon kepala daerah yaitu paling rendah 30 tahun untuk calon gubernur dan wakil gubernur, dan usia paling rendah 25 tahun untuk calon bupati dan wakil bupati serta calon walikota dan wakil walikota, yang dalam hal ini dihitung sejak penetapan pasangan calon karena telah melewati tahapan-tahapan Pilkada 2024. Penerapan Penelitian: Lembaga Negara dan Pemerintah diharapkan lebih teliti dalam menerbitkan penafsiran melalui putusan yang sama-sama bersifat final, mengikat, dan erga ormes, sehingga tidak terjadi adanya ketidakpastian hukum. Diharapkan adanya upaya harmonisasi peraturan untuk mencegah adanya dualism hukum, yang dapat menimbulkan konflik dan merugikan masyarakat. Kebaruan/Orisinalitas: Penelitian ini menelaah Putusan Mahkamah Agung Nomor 23P/HUM/2024 dan Putusan Mahkamah Konstitusi Nomor 70/PUU-XXII/2024 terkait ambang batas usia calon kepala daerah dan implikasi dari Putusan Mahkamah Agung Nomor 23P/HUM/2024 dan Putusan Mahkamah Konstitusi Nomor 70/PUU-XXII/2024 dalam menciptakan checks and balances di pemerintahan. Kata Kunci: Putusan, ambang batas usia, pemilihan kepala daerah, checks and balances